Collaborative Governance dalam Upaya Mengatur Pernikahan Dini di Kecamatan Rambah Hilir Kabupaten Rokan Hulu - Gayos Alfajri; Khotami Khotami (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to explore the implementation of collaborative governance in efforts to regulate early marriage in Rambah Hilir District, Rokan Hulu Regency. The ongoing occurrence of early marriage has prompted the need for joint action among various stakeholders, particularly the government, to address this issue. A qualitative method with a descriptive approach was employed in this study, using interviews, observations, and documentation as data collection techniques. The research is based on the collaborative governance theory proposed by (Ansell & Gash, 2008), which includes four key variables: starting conditions, facilitative leadership, institutional design, and the collaboration process. The findings reveal that the collaboration carried out by the Office of Religious Affairs (KUA) of Rambah Hilir District together with related stakeholders has not yet been fully effective. This is mainly due to the weak leadership role and suboptimal implementation in the field. However, the collaboration has contributed to reducing the rate of early marriage in the region. It is recommended that socialization and educational programs especially regarding the impacts of early marriage and sex education be intensified through the use of social media and that regular meeting agendas be established to enhance collaboration among stakeholders.